Hemlock Poisoning in Emergent Patients - Fuat Kulaksiz; Ali Kemal Erenler; Hasan Ozden; Mehmet Oğuzhan Ay; Ahmet Cinar Yasti (Global Journal of Rare Diseases - Peertechz Publications, 2016)
Background: Although poisoning from the ingestion of toxic plants is rarely encountered in Emergency Departments, it can cause serious complications and even death. It is difficult to recognize, diagnose, and differentiate if the patient is unconscious. Conium maculatum (poison Hemlock) is one of the most highly poisonous plants which can cause death due to respiratory failure. Clinical presentation may also be central nervous system depression, renal failure, rhabdomyolisis, and dermatitis. The similar shape and appearance of the plant to parsley can cause ingestion by mistake, which makes it difficult to obtain an accurate medical history from witnesses. Public awareness regarding mushroom poisoning is descriptive in the treatment of victims, however, patients and those accompanying them to hospital may not state the ingestion of the parsley-like poison Hemlock0. Case Reports : Two children were admitted to the Emergency Department (ED) with altered mental status, balance disorder and muscle spasms with irrelevant, non-specific medical histories. Their proper management was carried out by an emergency medicine physician who has previously experienced with an adult with respiratory distress and loss of consciousness with muscle spasms, dilated pupils and excessive secretion. Adult patient was immediately intubated for ventilatory support. After his full recovery, ingestion of hemlock poison was learned. As immediate diagnosis and prompt supportive treatment is the mainstay of treatment, an emergency physician should keep the possibility of Hemlock poisoning in mind for patients with respiratory failure.